2015
DOI: 10.1007/s10880-015-9431-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Quality of Life and Social Support in Inflammatory Bowel Disease

Abstract: Cognitive and social factors are essential considerations in inflammatory bowel disease (IBD) patient management, but existing research is limited. This study aims to expand the IBD literature by examining the relationship between social supports and QoL, while examining mechanisms in these relationships. Consenting patients attending an IBD outpatient clinic were provided a survey package (N = 164). Regressions evaluated predictors of IBD-QoL, and catastrophizing and optimism were examined as mediators betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 58 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…This study did not include a comparator disease group as there are no comparable comprehensive liver disease patient cohorts. However, work in inflammatory bowel disease (IBD) found that diminished IBD‐quality of life was predicted by younger age and social interaction variables were associated with IBD‐quality of life . In contrast, fatigue associated with renal transplantation has a greater symptomatic impact in older patients …”
Section: Discussionmentioning
confidence: 99%
“…This study did not include a comparator disease group as there are no comparable comprehensive liver disease patient cohorts. However, work in inflammatory bowel disease (IBD) found that diminished IBD‐quality of life was predicted by younger age and social interaction variables were associated with IBD‐quality of life . In contrast, fatigue associated with renal transplantation has a greater symptomatic impact in older patients …”
Section: Discussionmentioning
confidence: 99%
“…Social support, referred to as the support from family, friends and others, is identified as a protective factors for increased HRQoL across a variety of chronic diseases [24]. It was found that high levels of social support could help minimize pain and stress, provide a buffer against psychological distress, and enhance self-management [24]. Empirical studies have shown that IBD patients with lower perceived support had an impairment of HRQoL [13,24].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that high levels of social support could help minimize pain and stress, provide a buffer against psychological distress, and enhance self-management [24]. Empirical studies have shown that IBD patients with lower perceived support had an impairment of HRQoL [13,24]. However, literatures on the relationships between social support and IBD-related HRQoL were relatively lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This points to the significant role played by support networks in the lives of patients -on one hand, emotional support can help patients in everyday life, and on the other -the strength of the symptoms is strongly associated with the need for support. The described relationships were also The sense of coherence, social support and quality of life among patients with inflammatory bowel disease examined in other studies -it has been proven that the support provided by family, friends and others is significantly related to the quality of life of IBD patients [25]. Other studies have shown that perceived social support is a predictor of quality of life in patients with Crohn's disease and ulcerative colitis [23].…”
Section: Discussionmentioning
confidence: 89%